Novel Sampah di Laut, Meira karya Mawan Belgia: Kajian Ekologi Sastra - Dwi Rizka Aryanti (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2023)
This study aims to describe the impact of environmental damage and the author's interaction with the environment using literary ecology studies. The source of the research data is the Novel Sampah di Laut, Meira by Mawan Belgia totaling 246 pages published by Buku Mojok, first printing in April 2020. The data for this research is a form of literary ecology, namely the impact of environmental damage and the author's interaction with the environment contained in the Novel Novel Sampah di Laut, Meira by Mawan Belgia. The method used in this study is a qualitative descriptive method by collecting data, describing the data, and then analyzing the data. The research instrument used in this study was a documentation guide by reading and understanding the novel. The data analysis technique used is to read carefully, appreciate and understand, collect data, describe and conclude the results of the researcher. The results of this study found the impact of environmental damage consisting of water and soil pollution, declining economic conditions, and the extinction of fish populations. The results of the author's interaction are the author's interaction with social and the author's interaction with the state of the sea.